Prolegomena to Children’s Libraries in Response to Violence in Social Networks - Montero Bustabad, Pedro (2022)
The issue of violence in social networks is addressed through an approach and reflection based on the current context and its relationship with the formulation and work of the academic activity of the School of Librarianship, Documentation, and Information of the National University with the Biblioteca Infantil Miriam Álvarez Brenes (BIMAB), the only children’s library in Costa Rica. The suggestions made conclude a series of interdisciplinary actions under a collaborative work dynamic that the BIMAB could consider in its work as a measure to address this issue that directly affects children in conjunction with their parents or legal guardians.